Playing Expression Board: Developing Self-Awareness Skills for Children Aged 5 - 6 Years - Syarifah Halifah; Rismayanti Risma; Dewi Satriani (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
Children's self-awareness in Anugrah Kindergarten has not developed as it should. There are three child subjects in this study. The expression board game applied to this study is social play and playing with objects based on the explanation of the types of games that have been proposed. This study aims to analyze the development of self-awareness in group B children in Anugrah Kindergarten. The method carried out is qualitative with a qualitative descriptive approach. The techniques and data collection used in this study are observation, interview, and documentation techniques. Data analysis techniques use research instruments applied by researchers, namely observation sheets and anecdotal notes. The results showed that self-awareness can be developed through expression board game activities in children aged 5-6 at Anugrah Kindergarten in Parepare city.